Online and Collaborative Tools During Academic and Erasmus Studies - Oliveira, D. M. (2021)
The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2021 R. Babo et al. (eds.), Workgroups eAssessment: Planning, Implementing and Analysing Frameworks, Intelligent Systems Reference Library 199,